Diseño de un sistema de gestión basada en la metodología del balanced scorecard - González Correa, Dennys (2009)
The tesis developed below, was applied in Aseving SA, dedicated to the provision of security services. The organization adopted the Balanced Scorecard methodology through strategic Planning, wicth together make up a very useful tool for management and decision making in the organization.